(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
International Bank Guarantees Are A Commitment Of Signature Made By A Given Bank To Guarantee For The Beneficiary A Compensation Of Refund In Case The Contracting Party Does Not Fulfill Their Commitment Toward Him. The Commitment Made By The Guaranteeing Bank Is A Personal One. In Fact, The Bank Takes Charge Of Payment Of A Given Rate Of The Commercial Contract To The Ordering Customer, Whether It Is A Seller Or A Buyer, So That It Compensates The Beneficiary, Whether It Is A Seller Or A Buyer, If The Ordering Party Contravenes Their Commitment. In Banking Practice, There Are Many Types Of International Guarantees, But They Can Be Subdivided Into Three Legal Forms: The Security, Which Is A Personal One And Has A Nature Of Subordination To The Secured Obligation. This Type Of Guarantee Is Almost No More Used. The Second Type Is The Guarantee On Demand. It Is Independent Regarding The Original Contract. The Third One Is The Letter Of Credit. It Is Of A Double Nature Being In The Same Time A Guarantee On Demand And A Letter Of Credit Having The Form Of A Letter. Theses Guarantees Also Have Various Characteristics Making Theme Different From Many Similar Legal Systems, And Giving Them Importance And An Effective Role In Facilitating International Trade Transaction And In Enhancing Trust Between Operators Through The Coverage Of The Risk Of Breach By Any Party Of Its Obligations. This Consequently Contributes To Promote International Trade. Key Words - International Guarantees; Letter Of Credit; International Trade; Security.